(untitled) (Experimental biology, 2015)
Cytotoxic effect of carbonized rice husk (CRH) on fibroblasts of mice derma in T3B3 cell culture and processes of migration and proliferation of these cells in the presence of CRH were investigated. Received results showed that the application of CRH in sorption therapy for treatment of acute and chronic purulo-necrotic processes is innoxious and perspective.